Jahresgaben 1993 : Neuer Aachener Kunstverein. - NAK (Neuer Aachener Kunstverein), Aachen (Aachen : Neuer Aachener Kunstverein, 1993)
Bach, Michael ; Blume, Irene ; Dellbrügge / De Moll ; Falken, Herbert ; Gerwers, Martin ; Gursky, Andreas ; Herzog, Petra ; Hoffmann, Leni ; Nechvatal, Joseph ; Radermacher, Norbert ; Rosenthal, Andreas ; Sansoni, Andreas ; Virnich, Winfried
Duits
boek